The nonlinear impact of rural three-industry integration on agricultural non-point source pollution: its spatial effects and the moderating effect of environmental regulations - He, Guoping; Nong, Qinglian (Frontiers in Environmental Science, 2025)
A comprehensive examination of the impact of rural three-industry integration on agricultural non-point source pollution is essential for promoting sustainable agricultural development. This study employs panel data from 30 provinces in China (excluding Hong Kong, Macao, Taiwan, and Tibet) for the period 2011–2022. It adopts a two-way fixed effects model, a moderating effects model, and a spatial Durbin model to investigate the impact of rural three-industry integration on agricultural non-point source pollution, as well as its spatial spillover effects and the moderating role of environmental regulation. The results indicate that: (1) The effect of rural three-industry integration on agricultural non-point source pollution follows an inverted U-shaped pattern, with a turning point at an integration level of 0.29. As of 2022, most regions remain on the left side of the curve, suggesting a tendency for rural three-industry integration to exacerbate agricultural non-point source pollution. (2) All three types of environmental regulations weaken the effect of rural three-industry integration on agricultural non-point source pollution, but their moderating effects differ. Market-based and public-voluntary regulations shift the turning point of the curve to the left, bringing forward the stage at which integration begins to reduce pollution, whereas command-and-control regulations shift the turning point to the right, extending the stage in which integration intensifies pollution. (3) Rural three-industry integration has a significant spatial spillover effect on agricultural non-point source pollution. This study demonstrates the nonlinear characteristics and spatial effects of rural three-industry integration on agricultural non-point source pollution. It further clarifies the distinct roles of different types of environmental regulation in this relationship. The findings provide valuable guidance for policy formulation, promote the development of rural three-industry integration, and enhance its potential to reduce agricultural non-point source pollution.